Analisis Trend Penggunaan Tempat Tidur Berdasarkan Grafik Barber Johnson di Rumah Sakit Qim Batang Tahun 2018-2022 - Jihan Rizqi Kholda; Asih Prasetyowati; Reni Murnita; Andri Asmorowati (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2024)
The BOR, LOS, TOI, and BTO indicators at QIM Hospital in Batang are currently suboptimal, potentially contributing to issues like increased nosocomial infections and an incomplete view of service quality. This study aimed to analyze the trends of these indicators from 2018 to 2022 using a descriptive quantitative approach. Data were collected through observations and interviews with the reporting officer, focusing on Quality Indicator Reports for BOR, LOS, TOI, and BTO, along with secondary data on service indicators and TT availability. The analysis used Barber Johnson graphs and the least squares method. In 2018, BOR did not meet the Barber Johnson standard, but by 2019, it reached ideal levels, while LOS, TOI, and BTO remained suboptimal. The efficiency of BOR, LOS, TOI, and BTO declined from 2018-2020, improving in 2021. The trends from 2018-2025 for BOR and BTO showed positive shifts, while LOS and TOI continued to decline. The Barber Johnson chart indicated that from 2018-2022, QIM Hospital's performance remained outside the efficient zone, with projections suggesting the trends will persist. In conclusion, QIM Batang Hospital’s data management using Barber Johnson graphs is suboptimal. It is recommended that the hospital store data more efficiently and optimize services to meet ideal BOR targets in future years.